Heterogeneous metallaphotoredox catalysis in a continuous-flow packed-bed reactor - Hsu, Wei-Hsin; Reischauer, Susanne; Seeberger, Peter H.; Pieber, Bartholomäus; Cambié, Dario (Beilstein Journal of Organic Chemistry, 2022)
Metallaphotoredox catalysis is a powerful and versatile synthetic platform that enables cross-couplings under mild conditions without the need for noble metals. Its growing adoption in drug discovery has translated into an increased interest in sustainable and scalable reaction conditions. Here, we report a continuous-flow approach to metallaphotoredox catalysis using a heterogeneous catalyst that combines the function of a photo- and a nickel catalyst in a single material. The catalyst is embedded in a packed-bed reactor to combine reaction and (catalyst) separation in one step. The use of a packed bed simplifies the translation of optimized batch reaction conditions to continuous flow, as the only components present in the reaction mixture are the substrate and a base. The metallaphotoredox cross-coupling of sulfinates with aryl halides was used as a model system. The catalyst was shown to be stable, with a very low decrease of the yield (≈1% per day) during a continuous experiment over seven days, and to be effective for C–O arylations when carboxylic acids are used as nucleophile instead of sulfinates.
Keywords: flow chemistry; heterogeneous catalysis; metallaphotoredox catalysis; packed bed; photochemistry

(untitled) - Shaw, M. H.; Twilton, J.; MacMillan, D. W. C. (J. Org. Chem., 2016)

(untitled) - Marzo, L.; Pagire, S. K.; Reiser, O.; König, B. (Angew. Chem., Int. Ed., 2018)

(untitled) - Buglioni, L.; Raymenants, F.; Slattery, A.; Zondag, S. D. A.; Noël, T. (Chem. Rev., 2022)

(untitled) - Cambié, D.; Bottecchia, C.; Straathof, N. J. W.; Hessel, V.; Noël, T. (Chem. Rev., 2016)

(untitled) - Plutschack, M. B.; Pieber, B.; Gilmore, K.; Seeberger, P. H. (Chem. Rev., 2017)

(untitled) - Bottecchia, C.; Lévesque, F.; McMullen, J. P.; Ji, Y.; Reibarkh, M.; Peng, F.; Tan, L.; Spencer, G.; Nappi, J.; Lehnherr, D.; Narsimhan, K.; Wismer, M. K.; et al. (Org. Process Res. Dev., 2022)

(untitled) - Steiner, A.; Roth, P. M. C.; Strauss, F. J.; Gauron, G.; Tekautz, G.; Winter, M.; Williams, J. D.; Kappe, C. O. (Org. Process Res. Dev., 2020)

(untitled) - Halperin, S. D.; Kwon, D.; Holmes, M.; Regalado, E. L.; Campeau, L.-C.; DiRocco, D. A.; Britton, R. (Org. Lett., 2015)

(untitled) - Skubi, K. L.; Blum, T. R.; Yoon, T. P. (Chem. Rev., 2016)

(untitled) - Chan, A. Y.; Perry, I. B.; Bissonnette, N. B.; Buksh, B. F.; Edwards, G. A.; Frye, L. I.; Garry, O. L.; Lavagnino, M. N.; Li, B. X.; Liang, Y.; Mao, E.; Millet, A.; et al. (Chem. Rev., 2022)

(untitled) - Abdiaj, I.; Alcázar, J. (Bioorg. Med. Chem., 2017)

(untitled) - González-Esguevillas, M.; Fernández, D. F.; Rincón, J. A.; Barberis, M.; de Frutos, O.; Mateos, C.; García-Cerrada, S.; Agejas, J.; MacMillan, D. W. C. (ACS Cent. Sci., 2021)

(untitled) - Harper, K. C.; Moschetta, E. G.; Bordawekar, S. V.; Wittenberger, S. J. (ACS Cent. Sci., 2019)

(untitled) - Lima, F.; Kabeshov, M. A.; Tran, D. N.; Battilocchio, C.; Sedelmeier, J.; Sedelmeier, G.; Schenkel, B.; Ley, S. V. (Angew. Chem., Int. Ed., 2016)

(untitled) - Vaccaro, L.; Lanari, D.; Marrocchi, A.; Strappaveccia, G. (Green Chem., 2014)

(untitled) - Thomson, C. G.; Lee, A.-L.; Vilela, F. (Beilstein J. Org. Chem., 2020)

(untitled) - Pieber, B.; Shalom, M.; Antonietti, M.; Seeberger, P. H.; Gilmore, K. (Angew. Chem., Int. Ed., 2018)

(untitled) - Chaudhuri, A.; Zondag, S. D. A.; Schuurmans, J. H. A.; van der Schaaf, J.; Noël, T. (Org. Process Res. Dev., 2022)

(untitled) - Rosso, C.; Gisbertz, S.; Williams, J. D.; Gemoets, H. P. L.; Debrouwer, W.; Pieber, B.; Kappe, C. O. (React. Chem. Eng., 2020)

(untitled) - Debrouwer, W.; Kimpe, W.; Dangreau, R.; Huvaere, K.; Gemoets, H. P. L.; Mottaghi, M.; Kuhn, S.; Van Aken, K. (Org. Process Res. Dev., 2020)

(untitled) - Bottecchia, C.; Erdmann, N.; Tijssen, P. M. A.; Milroy, L.-G.; Brunsveld, L.; Hessel, V.; Noël, T. (ChemSusChem, 2016)

(untitled) - Abramov, A.; Bonardd, S.; Pérez‐Ruiz, R.; Díaz Díaz, D. (Adv. Synth. Catal., 2022)

(untitled) - Vijeta, A.; Casadevall, C.; Reisner, E. (Angew. Chem., 2022)

(untitled) - Wen, Z.; Wan, T.; Vijeta, A.; Casadevall, C.; Buglioni, L.; Reisner, E.; Noël, T. (ChemSusChem, 2021)

(untitled) - Zhao, X.; Deng, C.; Meng, D.; Ji, H.; Chen, C.; Song, W.; Zhao, J. (ACS Catal., 2020)

(untitled) - Vijeta, A.; Casadevall, C.; Roy, S.; Reisner, E. (Angew. Chem., Int. Ed., 2021)

(untitled) - Gisbertz, S.; Pieber, B. (ChemPhotoChem, 2020)

(untitled) - Cavedon, C.; Gisbertz, S.; Vogl, S.; Richter, N.; Schrottke, S.; Teutloff, C.; Seeberger, P. H.; Thomas, A.; Pieber, B. (ChemRxiv, 2021)

(untitled) - Tobin, J. M.; Liu, J.; Hayes, H.; Demleitner, M.; Ellis, D.; Arrighi, V.; Xu, Z.; Vilela, F. (Polym. Chem., 2016)

(untitled) - Kong, C. J.; Fisher, D.; Desai, B. K.; Yang, Y.; Ahmad, S.; Belecki, K.; Gupton, B. F. (Bioorg. Med. Chem., 2017)

(untitled) - Wong, Y.-L.; Tobin, J. M.; Xu, Z.; Vilela, F. (J. Mater. Chem. A, 2016)

(untitled) - Tobin, J. M.; McCabe, T. J. D.; Prentice, A. W.; Holzer, S.; Lloyd, G. O.; Paterson, M. J.; Arrighi, V.; Cormack, P. A. G.; Vilela, F. (ACS Catal., 2017)

(untitled) - Woźnica, M.; Chaoui, N.; Taabache, S.; Blechert, S. (Chem. – Eur. J., 2014)

(untitled) - Rodriguez-Zubiri, M.; Felpin, F.-X. (Org. Process Res. Dev., 2022)

Flowchem, v. 0.0.8, 2022 (Cambié, D.; Wolf, J.; Wei-Hsin, H)

(untitled) - Helmus, J. J.; Jaroniec, C. P. (J. Biomol. NMR, 2013)

(untitled) - Barreiro, E. M.; Hao, Z.; Adrio, L. A.; van Ommen, J. R.; Hellgardt, K.; Hii, K. K. (Mimi). (Catal. Today, 2018)

(untitled) - Cantillo, D.; Kappe, C. O. (ChemCatChem, 2014)

(untitled) - Baxendale, I. R.; Ley, S. V.; Mansfield, A. C.; Smith, C. D. (Angew. Chem., Int. Ed., 2009)

(untitled) - Hessel, V.; Löwe, H.; Schönfeld, F. (Chem. Eng. Sci., 2005)

(untitled) - Hardt, S.; Drese, K. S.; Hessel, V.; Schönfeld, F. (Microfluid. Nanofluid., 2005)

(untitled) - Ghanem, A.; Lemenand, T.; Della Valle, D.; Peerhossaini, H. (Chem. Eng. Res. Des., 2014)

Handbook of Industrial Mixing - Etchells, A. W., III; Meyer, C. F. (Mixing in Pipelines, 2003)

(untitled) - Schwolow, S.; Hollmann, J.; Schenkel, B.; Röder, T. (Org. Process Res. Dev., 2012)

(untitled) - Yazdanpanah, N.; Cruz, C. N.; O'Connor, T. F. (Comput. Chem. Eng., 2019)